Expert-Driven Criteria for Assessing SME Readiness for Open Data: Insights from an AI-Supported Brainstorming Workshop - Škraba, Andrej; Pucihar, Andreja; Blatnik, Staša; Čelik, Nejc; Lavrič, Franc; Stojanović, Radovan; Kljajić Borštnar, Mirjana (39th Bled eConference: Co-Creating Human-Centred and Responsible Digital Futures; Conference Proceedings, 2026)
The growing importance of open data ecosystems highlights the need for SMEs to assess their maturity for open data use. This study presents findings from an expert workshop aimed at identifying the factors that drive or hinder SME open data maturity. The workshop, conducted at the 37th Bled eConference, involved 17 experts in a structured brainstorming session supported by the Kresilnik digital tool. A total of 260 ideas were generated through a two-phase process combining traditional ideation and AI-supported suggestion generation. The results indicate that AI assistance can mitigate the typical decline in brainstorming productivity by shifting participant roles toward evaluation and refinement of generated ideas. In addition to methodological insights into human–AI collaborative ideation, the study proposes a structured set of expert-derived criteria for assessing SME maturity for open data. The findings demonstrate the potential of hybrid brainstorming approaches for rapid knowledge generation in emerging digital transformation domains.